2020
DOI: 10.1074/jbc.ra119.011487
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor targets hepatocyte nuclear factor 4α and mediates protective effects of vitamin D in nonalcoholic fatty liver disease

Abstract: Epidemiological studies have suggested a link between vitamin D deficiency and increased risk for nonalcoholic fatty liver disease (NAFLD); however, the underlying mechanisms have remained unclear. Here, using both clinical samples and experimental rodent models along with several biochemical approaches, we explored the specific effects and mechanisms of vitamin D deficiency in NAFLD pathology. Serum vitamin D levels were significantly lower in individuals with NAFLD and in high-fat diet (HFD)-fed mice than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 57 publications
1
53
0
1
Order By: Relevance
“…Male C57BL/6 mice (6-8 weeks old) were purchased from the Nanjing Biomedical Research Institution of Nanjing University (Nanjing, China) and housed in Zhejiang Academy of Medical Sciences with a 12-h light/dark cycle in a temperature-controlled environment with regular chow and water. For the vitamin D diet experiment, C57BL/6 mice were fed a diet containing 2000/4000 IU of vitamin D or a vitamin D-deficient diet after being weaned and were maintained on this diet until the end of the 9-week DSS administration (22,54). The vitamin D-sufficient/deficient diet and the corresponding control diet were purchased from Shuyishuer Bio (Changzhou, China).…”
Section: Micementioning
confidence: 99%
“…Male C57BL/6 mice (6-8 weeks old) were purchased from the Nanjing Biomedical Research Institution of Nanjing University (Nanjing, China) and housed in Zhejiang Academy of Medical Sciences with a 12-h light/dark cycle in a temperature-controlled environment with regular chow and water. For the vitamin D diet experiment, C57BL/6 mice were fed a diet containing 2000/4000 IU of vitamin D or a vitamin D-deficient diet after being weaned and were maintained on this diet until the end of the 9-week DSS administration (22,54). The vitamin D-sufficient/deficient diet and the corresponding control diet were purchased from Shuyishuer Bio (Changzhou, China).…”
Section: Micementioning
confidence: 99%
“…Surprisingly, we found not only lower levels of 25(OH)D 3 -d 3 in serum, but also in the livers of Cd36 -/mice which are not indicative of an impaired transfer of this vitamin D metabolite into the circulation. Interestingly, low serum levels of 25(OH)D have also been observed in patients suffering from nonalcoholic liver diseases compared to those of healthy subjects and in mice developing fatty livers in response to a high-fat diet compared to those fed a standard chow diet [44]. Thus, we may speculate that the accumulation of liver lipids in the Cd36 -/mice could have hampered the 25(OH)D synthesis, although the mRNA abundance of the vitamin D hydroxylases in the livers are not indicative of an affected expression of these enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D has been shown to enhance insulin sensitivity in vitro through upregulation of GLUT4 and modification of free fatty acids metabolism ( 145 ). Preclinical studies suggest potential anti-inflammatory, antiproliferative, and antifibrotic effects of vitamin D administration on the liver in vivo ( 146 , 147 ). Small-scale randomized controlled trials have shown that vitamin D supplementation improves the metabolic syndrome ( 148 , 149 , 150 ).…”
Section: Growth Hormone Dysregulationmentioning
confidence: 99%